Survival of Vibrio spp. including inoculated V. cholerae 0139 during heat-treatment of cockles (Anadara granosa) - Liew, W. S.; Leisner, Jorgen Johannes; Rahmat Ali, Gulam Rusul; Radu, Son; Che Nun, Abdul Rassip (Elsevier Science, 1998)
The effect of heat-treatment on the internal temperature of raw cockles (Anadara granosa) and survival of their intrinsic flora of Vibrio spp. as well as of inoculated V. cholerae 0139 was examined. The cockles were purchased from markets in Malaysia and had an average weight including shells of 8.90±2.45 g. In one experiment heatpenetration of individual cockles was examined. Cockles weighing <8 g (including shell) exhibited maximum internal temperatures of between 50 and 75°C when heated in water at 99°C for 10 s and 71–93°C when heated for 30 s. Cockles weighing >12 g exhibited maximum internal temperatures between 42 and 58°C when heated in water at 99°C for 10 s and 56–69°C when heated for 30 s. In another experiment, heat-treatment of 10 cockles treated as a group at 99°C for 10 or 30 s resulted in reduction of levels of intrinsic Vibrio spp. (enumerated directly on thiosulphate–citrate–bile salt sucrose agar; TCBS) from 5.73 to 3.15 log cfu g−1 or below 1 log cfu g−1, respectively. The levels of Vibrio spp. after heat-treatment decreased with an increase in numbers of cockles grouped together during treatment. In a third experiment V. cholerae 0139 was inoculated into cockles and subjected to heat-treatment at 99°C for 0, 10, 15, 20, 25 or 30 s. The levels of Vibrio spp. in uninoculated, non-heat-treated cockles was 4.89 log cfu g−1 on TCBS, and the predominant species were V. parahaemolyticus and V. alginolyticus. V. cholerae 0139 inoculated into cockles with an average weight of 13.5±1.90 g (including shell) decreased for samples examined immediately after heat-treatment from 6 log cfu g−1 initially to 3.5 log cfu g−1 after 25 s and <1 log cfu g−1 (TCBS) after 30 s of heat-treatment. The most probable number method by enrichment in alkaline peptone water gave in general within 1 log unit higher counts than TCBS direct enumeration. TCBS direct enumeration and MPN counts were up to 2.38 or 1.30 log units higher, respectively, for samples heat-treated for 20 s or longer and stored for 6 h at 30°C before examination, than for samples heat-treated for same periods of time and examined immediately. This study shows that a mild heat-treatment of cockles for up to 25 s is inadequate to ensure a large reduction in numbers of Vibrio spp., including V. cholerae 0139.